PERUBAHAN KEBIJAKAN MIGRANT PROTECTION PROTOCOLS AMERIKA SERIKAT PADA ERA PEMERINTAHAN JOE BIDEN - Nurinsa Afrina; Tuah Kalti Takwa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
ABSTRACT The Migrant Protection Protocols, better known as “Remain in Mexico,” were an immigration policy implemented during the Trump administration that required undocumented immigrants to wait in Mexico while their asylum claims were processed. Its strict implementation drew widespread criticism due to humanitarian concerns, including substandard living conditions, limited access to legal aid, and a high risk of violence. In contrast, the Biden administration has sought to reform the policy with a more humane approach. This study employs a qualitative approach, utilizing data collection techniques based on a literature review drawn from books, journals, websites, official documents, and reports from relevant institutions. The study applies Charles F. Hermann’s Theory of Foreign Policy, which encompasses four levels of change adjustment changes, program changes, problem/goal changes, and international orientation changes as well as the State Analysis Level. The results indicate that changes to the MPP under the Biden administration have occurred gradually across all four levels, ranging from the suspension of new registrations, modifications to immigration policy programs, shifting policy objectives toward a more humane approach, to improvements in relations between the U.S. and Mexico as well as Central American nations. The Biden administration’s actions include executive orders focused on evaluating and transitioning away from MPP, facilitating the return of asylum seekers to the U.S., and expanding humanitarian parole programs. Keywords: Joe Biden, Immigration Policy, Migrant Protection Protocols, Immigrant, U.S.-Mexico Border